A conceptual framework for the process protocol of integration quality, safety, health and sustainable construction management systems for infrastructure projects in Indonesia - Dewi Arman Utami; Suraji Akhmad; Hidayat Benny (E3S Web of Conferences)
Construction accidents on infrastructure projects in Indonesia from 2017-2021 have increased by 5.65% from previous years. Construction accidents that result in property damage, death or injury to both workers and the public, pollution and environmental damage cause sustainable development goals not to be achieved. Construction accidents are not only focused on the impacts, but it is necessary to explore how the incident occurred. This is the basis for the need to integrate quality, safety, health and sustainability in construction. The current construction safety management system is not yet integrated with other management systems. This paper aims to develop a conceptual framework in the process of integrating construction quality, safety, health and sustainability management systems. Development of a conceptual framework based on literature review, ISO standards and existing construction safety planning guidelines. The development of this conceptual framework is part of a research proposal that is being formulated to develop a process protocol for integrating process of construction quality, safety, health and sustainability management systems in infrastructure projects. This process protocol can simplify the complexity and overlapping of the processes of each management system so that it is easier to understand and to implement by all project stakeholders.